An Explicative Review on the Progress of Quinazoline Scaffold as Bioactive Agents in the Past Decade - Jain, Naman; Goel, Tanvi; Thakar, Snehal; Jadhav, Madhav; Bansode, Deepali (Medicinal Chemistry, 2023)
In the last decade, quinazoline has been one of the most explored scaffolds by researchers around the globe in medicinal chemistry. Its unique structural features provide a wide range of substitutions for nitrogen and carbonyl groups. In the current situation of COVID-19, hydroxychloroquine, an antimalarial drug of the quinoline category, was used for the treatment of severe infections. Various substitution patterns, hybrids, and conjugates of quinazoline have been developed and studied for various pharmacological activities like anticancer, anti-inflammatory, antimalarial, antitubercular, etc. The scaffold can be considered a potential molecule for various pharmacological activities, especially antimicrobial and anti-hypertensive. This review article aims to study the physicochemical properties, chemistry, and pharmacological profile of quinazoline.
Keywords: marketed drugs